(untitled) (World Bulletin of Public Health, 2022)
"Overweight" technically refers to an excess of body weight, whereas "obesity" refers to an excess of fat.Childhood obesity is a growing problem and an increasing public health concern in the developed countries. Even more worrying is the increasing prevalence of obesity in developing countries. Childhood obesity is a well-recognized problem all over the world. Obesity can cause other medical problems in childhood, adolescence and adulthood